Factors Influencing the Aspirations of FirstYear Engineering Students: A Statistical Study - Joshi, Ajinkya S.; Shahabadkar, Pramod K.; Nandurkar, Keshav N.; Jawale, Dnyaneshwaree S. (Journal of Engineering Education Transformations, 2025)
An engineering student passing out from the college has different aspirations such as obtaining a job through campus interview, opting for higher education in India and abroad, becoming an entrepreneur and so on. A study was conducted in the past to understand the aspirations of the undergraduate students. The current study is an attempt to identify the factors that influence the student aspirations. A study in this connection was carried out in an Engineering College located in the western part of India. The objective of this paper is to determine the factors influencing the aspirations of engineering students. Nine factors influencing the student aspirations were identified from the findings of the previous study and additional six factors were identified through a brainstorming session with the faculty members and students. A Google form was created to identify the prominent factors influencing the student aspirations. This form was circulated to 450 students and responses were obtained from 286 students over a period of one month. Multiple Linear Regression analysis was used to identify the most significant factors that influenced the student aspirations. Results indicate that seven factors namely annual family income, peer motivation, chances of fulfillment of aspirations, government policies, current academic marks, opportunities provided by institute and marks in CET exam are the most influential shaping the student aspirations. The outcome of this study will help the educational institutions to channelize their efforts, develop suitable mechanisms and help the students in fulfilling their aspirations.